Social wasp guild ( Hymenoptera: Vespidae) visiting flowers in two of the phytophysiognomic formations: Riparian Forest and campos rupestres - Clemente, M. A.; Campos, N. R.; Vieira, K. M.; Del-Claro, K.; Prezoto, F. (Univ Estadual Feira Santana, 2017)
Social wasps are part of the floral visitor guild. In this study, we investigated the distribution of flower-visiting wasp species in two phytophysiognomies in the State Park of Ibitipoca, Minas Gerais, Brazil. We inspected flowering plants with visiting wasps along a 1 km transect in riparian forest and another 1 km transect in campos rupestres over the course of one year, for a total sampling effort of 240 hours. We found a total of 103 individuals with 15 species distributed among 7 genera, the most common belonging to the Erythroxylaceae (n = 10) and Asteraceae (n = 10) families. Asteraceae had the highest abundance (n = 55). The diversity and evenness of these insects was higher in riparian forest (H '= 0.78 and J' = 0.75) than in campos rupestres (H '= 0.30, J' = 0.39). All species visited flowers of 19 plant species in riparian forest, and eight wasp species visited 11 plant species in campos rupestres. These Polistinae acted as regular floral visitors, thus, conservation programs in these areas may be relevant for the maintenance of social wasp diversity.
Keywords: Trophic niche; pollinators; richness; abundance